Potential Mechanisms Involved in the Protective Effect of Dicaffeoylquinic Acids from Artemisia annua L. Leaves against Diabetes and Its Complications - Hesham El-Askary; Heba H. Salem; Amira Abdel Motaal (Molecules, 2022)
Diabetes mellitus is a chronic disease affecting the globe and its incidence is increasing pandemically. The use of plant-derived natural products for diabetes management is of great interest. Polar fraction of Artemisia annua L. leaves has shown antidiabetic activity in vivo. In the present study, three major compounds were isolated from this polar fraction; namely, 3,5-dicaffeoylquinic acid (1); 4,5-dicaffeoylquinic acid (2), and 3,4- dicaffeoylquinic acid methyl ester (3), using VLC-RP-18 and HPLC techniques. The potential protective effects of these compounds against diabetes and its complications were investigated by employing various in vitro enzyme inhibition assays. Furthermore, their antioxidant and wound healing effectiveness were evaluated. Results declared that these dicaffeoylquinic acids greatly inhibited DPPIV enzyme while moderately inhibited α-glucosidase enzyme, where compounds 1 and 3 displayed the most prominent effects. In addition, compound 3 showed pronounced inhibition of α-amylase enzyme. Moreover, these compounds markedly inhibited aldose reductase enzyme and exerted powerful antioxidant effects, among which compound 3 exhibited the highest activity implying a notable potentiality in impeding diabetes complications. Interestingly, compounds 2 and 3 moderately accelerated scratch wound healing. Our findings suggest that these dicaffeoylquinic acids can be promising therapeutic agents for managing diabetes and its complications.